Hidden Appendicoliths and Their Impact on the Severity and Treatment of Acute Appendicitis - Dölling, Maximilian; Rahimli, Mirhasan; Pachmann, Jonas; Szep, Malik; Al-Madhi, Sara; Andric, Mihailo; Kahlert, Ulf D.; Hofmann, Tobias; Boettcher, Michael; Munoz, Luis Enrique; Herrmann, Martin; Perrakis, Aristotelis; et al. (Journal of Clinical Medicine, 2024)
Background/Objectives: In patients diagnosed with uncomplicated acute appendicitis (UAA), the absence of calcified deposits or stones, called appendicoliths, often leads to consideration of non-operative treatment (NOT), despite the notable treatment failure rate associated with this approach. Previous research has indirectly estimated the prevalence of appendicoliths to range between 15% and 38% retrospectively by CT scan, intraoperative palpation, and pathology report, thereby potentially missing certain concrements. Our hypothesis proposes that this reported prevalence significantly underestimates the occurrence of appendicoliths, which could explain the high failure rate of 29% of patients with appendicitis observed with NOT. Methods: In our prospective study, conducted with a cohort of 56 adult patients diagnosed with acute appendicitis (AA), we employed intraoperative extracorporeal incisions of the vermiform appendix, in addition to standard diagnostic methods. Results: Our findings revealed 50% more appendicoliths by intraoperative incision (n = 36, p < 0.001) compared to preoperative imaging (n = 24). Appendicoliths were present in 71.4% (n = 40, p < 0.001) of AA patients. Conclusions: These results suggest that conventional diagnostic procedures plausibly underestimate the actual prevalence of appendicoliths, potentially elucidating the frequent treatment failures observed in NOT approaches applied to patients with UAA.
CRIS-Team Scopus Importer:2024-08-23
Keywords: acute appendicitis; appendicoliths; faecoliths; perforated appendicitis